Konsep Istiqamah Dalam Islam - Pathur Rahman (Jurnal Studi Agama, 2018)
Human life has not all come down to even more improvements that lead to destruction and destruction. This is due to a lack of determination (Istiqamah). Islamic education wants to create a place towards achieving benefits for humans themselves. Istiqamah attitude is obtained by doing something optimally, in accordance with science, not excessive, and sincerely selfless. With istiqamah it will produce a struggling yet calm and optimistic person. These three things will lead someone to the goal of Islamic education as a servant of Allah, as a caliph, and also happiness of the world and the hereafter.